2017
DOI: 10.3390/su9091499
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Urban Expansion in Lhasa City and the Implications for Sustainable Development in a Plateau City

Abstract: Urbanization challenges regional sustainable development, but a slight expansion mechanism was revealed in a plateau city. We have integrated the urban expansion process and analyzed its determinants in Lhasa (Tibet), and we provide insightful suggestions for urban management and planning for Lhasa. The full continuum of the urban expansion process has been captured using time-series of high-resolution remote sensing data . Four categories of potential determinants involved in economic, demographic, social, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 83 publications
0
26
0
2
Order By: Relevance
“…The early stage of the development of China's western region is primarily explained by the natural environment and governmental policies; macroscopic development of the area was controlled and guided by the government's policies and was extremely sensitive to administrative policies in China (Gao, Wei, Chen, & Komali, ; Tang, Zhou, Sun, Li, & Li, ). Development of the West Region , a great strategic vision, commenced in 2000, and this saw economic development in the western provinces continuously promoted through the considerable investment of national capital (Shi, Yang, & Hu, ).…”
Section: Discussionmentioning
confidence: 99%
“…The early stage of the development of China's western region is primarily explained by the natural environment and governmental policies; macroscopic development of the area was controlled and guided by the government's policies and was extremely sensitive to administrative policies in China (Gao, Wei, Chen, & Komali, ; Tang, Zhou, Sun, Li, & Li, ). Development of the West Region , a great strategic vision, commenced in 2000, and this saw economic development in the western provinces continuously promoted through the considerable investment of national capital (Shi, Yang, & Hu, ).…”
Section: Discussionmentioning
confidence: 99%
“…The implications of "Accelerated Urban Expansion in Lhasa City and the Implications for Sustainable Development in a Plateau City' are discussed by Wei Tang, Tiancai Zhou, Jian Sun, Yurui Li and Weipeng Li [5]. They explore the question of challenges urbanization causes for a plateau city of Lhasa.…”
Section: How To Pre-empt Nascent Risks and Threats In Villages By Mapmentioning
confidence: 99%
“…Min Yin believes that the rapid increase of population urbanization and the rapid development of tourism will surpass the environmental carrying capacity of the city, which is unconducive to the sustainable development of regional tourism [8]. Wei Tang found through empirical analysis that the development of tourism plays an important role in promoting urban expansion in the east and south of Lhasa [9]. Akama found that only by paying attention to the economic, social, and cultural interests of community residents can the coordinated development of urbanization and tourism be guaranteed [10].…”
Section: Coupling Between Tourism Industry and Urbanizationmentioning
confidence: 99%